2022
DOI: 10.1109/taffc.2022.3190233
|View full text |Cite
|
Sign up to set email alerts
|

Training Socially Engaging Robots: Modeling Backchannel Behaviors with Batch Reinforcement Learning

Abstract: A key aspect of social human-robot interaction is natural non-verbal communication. In this work, we train an agent with batch reinforcement learning to generate nods and smiles as backchannels in order to increase the naturalness of the interaction and to engage humans. We introduce the Sequential Random Deep Q-Network (SRDQN) method to learn a policy for backchannel generation, that explicitly maximizes user engagement. The proposed SRDQN method outperforms the existing vanilla Q-learning methods when evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Other methods train on hand-crafted examples through generative models [28,42]. For instance, predicting when to use backchanneling behaviors (i.e., providing feedback during conversation such as by nodding) has been learned through batch reinforcement learning [17] and recurrent neural networks [31]. Lastly, recent work has investigated how to learn cost functions for a target emotion from user feedback [49], or even learn an emotive latent space to model many emotions [40].…”
Section: Related Workmentioning
confidence: 99%
“…Other methods train on hand-crafted examples through generative models [28,42]. For instance, predicting when to use backchanneling behaviors (i.e., providing feedback during conversation such as by nodding) has been learned through batch reinforcement learning [17] and recurrent neural networks [31]. Lastly, recent work has investigated how to learn cost functions for a target emotion from user feedback [49], or even learn an emotive latent space to model many emotions [40].…”
Section: Related Workmentioning
confidence: 99%
“…Ding et al [10] describes how an agent can be endowed to elicit conversations with older adults for delivering cognitive training. Similarly, Hussain et al [14] presented a method that learnt to produce non-verbal backchannels, and demonstrated how such feedback had an impact on participants' engagement. Inden et al [16] modelled five different strategies for feedback behaviour in a conversational agent and evaluated their effectiveness in a user study, showing that when the robot took into account the interlocutor's utterance and pauses, participants rated that strategy as more adequate than the others.…”
Section: Introductionmentioning
confidence: 99%